Synthesis of Stimuli Responsive Graft Triblock Polymers via Combination of Reversible Addition-Fragmentation Chain Transfer Polymerization and Ring Opening Polymerization - Wu, Chenglin; Ying, Anguo; Ren, Shibin (Asian Journal of Chemistry, 2013)
A well-defined triblock copolymer, poly(ethylene glycol)-b-poly(2-hydroxyethyl methacrylate-g-lactide)-b-poly(N-isopropylacrylamide) [PEG-P(HEMA-PLA)-PNIPAM], containing a biodegradable PLA block and a thermo-sensitive PNIPAM block, was synthesized by a combination of ring opening polymerization (ROP) and reversible addition-fragmentation chain transfer polymerization (RAFT). The copolymer could self-assemble into core-shell micelles with PLA block as the core and PEG/PNIPAM blocks as the mixed shell at ambient temperature. With increasing temperature, the micelles converted into the core-shell-corona (CSC) structure because of the collapsed PNIPAM block. Dynamic light scattering shows that the hydrodynamic diameter (Dh) of the micelles is about 140 nm at low temperature (25 ºC) and 110 nm at high temperature (45 ºC).